Changing clinical significance of oocyte maturity grades with advancing female age advances precision medicine in IVF - Cari Nicholas; Sarah Darmon; Pasquale Patrizio; David F. Albertini; David H. Barad; Norbert Gleicher (iScience, 2023)
Summary: In current IVF practice, metaphase-2 (M2) oocytes are considered most efficient in producing good quality embryos. Maximizing their number at all ages is standard clinical practice, while immature germinal vesicle (GV) oocytes are mostly automatically discarded. We present preliminary evidence that oocyte maturity grades with advancing age significantly change in their abilities to produce good quality embryos, with M2 oocytes significantly declining, GV oocytes improving, and M1 oocytes staying the same. These data contradict the over-40-year-old dogma that oocyte grades functionally do not change with advancing age, supporting potential changes to current IVF practice: (1) Stimulation protocols and timing of oocyte retrieval can be adjusted to a patient’s age and ovarian function. (2) In older and younger women with prematurely aging ovaries, GV oocytes may no longer be automatically discarded. (3) In some infertile women, rescue in vitro maturation of immature oocytes may delay the need for third-party egg donation.